Determinan Pembiayaan Murabahah di BPRS Niaga Madani kota Makassar Periode 2023 - Syamsurianto, Syamsurianto; Misbach, Irwan; Bin Sapa, Nasrullah (Al-Buhuts, 2024)
Murabahah financing is one of the most dominant financing in the scope of Islamic banks in Indonesia. Murabahah financing dominates because financing provides a high level of trust for its customers. Because the acquisition price and profit are mutually agreed upon with the bank. In addition, the bank also feels favored. The dominance of Murabaha financing compared to profit-sharing financing such as Mudaraba and Partnership is clear for researchers to look for factors that influence Murabahah financing. This type of research is quantitative which is associative, In this case the author uses a quantitative method and the type of data in this study is secondary data in the form of time-series. The population used is a financial report based on quarters at BPRS Madani for the period 2017-2023 where the total is 27 financial reports for 1 year. The sample selection uses a saturated sample where all the population is used as a sample, which will later be processed using statistical analysis tools to get answers to the proposed hypothesis.Research results Based on the data test that has been carried out with a significance level of 5% or 0.05, it can be concluded that Non-performing financing has a positive and significant effect on Murabahah financing at BPRS Niaga Madani. Rotation on assets and financing to deposit ratio have a positive and insignificant effect on Murabahah financing of financing banks at BPRS Niaga Madani in the 2023 period.Conclusion Based on the results of the analysis and discussion that have been presented in the previous section, it can be concluded that non-performing financing has a significant positive effect on Murabahah financing at Bank Pembiayaan Rakyat Syariah Niaga Madani. This finding explains that the increasing non-performing finance of BPRS Niaga Madani will also increase the level of financing provided by BPRS Niaga Madani, this shows that the public increasingly trusts BPRS Niaga Madani so that what is the obligation of the community is still fulfilled even though some customers are hampered in returning financing. Rotation on assets and financing to deposit ratio have a positive and insignificant effect on Murabahah financing. that bank management is able to manage the assets owned by the company, so that the income generated experiences a better increase